Testicular Morphohistology of Hypsiboas pulchellus (Amphibia, Hylidae) During the Breeding Season (2015)
In this study, data concerning to the morphological testicular features of Hypsiboas pulchel-lus during the breeding season is provided, in order to know aspects of their reproductive biology. The testis, ovoid and yellowish with 4.64 ± 0.48 mm length and 2.05 ± 0.23 mm wide, are surrounded by the tunica albuginea which measures 5.60 ± 0.82 µm. The seminif-erous locules, placed internally, measure 257.47 ± 58.25 µm in diameter, and cysts with spermatogenic cells associated with Sertoli cells are distinguished in them. The interstitial tissue is scarce. The biggest cells of the germinal series are the spermatogonia I (14.34 ± 1.74 µm), from which spermatogonia II (10.14 ± 1.33 µm) originate. Spermatocytes I measure 9.34 ± 0.32 µm and have slightly condensed chromatin. The spermatocytes II are 8.12 ± 1.07 µm long. The spermatids I are spherical, grouped in rounded cysts, and measure 7.61 ± 1.45 µm. On the other hand, spermatids II are elongated (4.09 ± 0.51 µm) and not within the cysts. Towards the center of the loculus, the free, lengthened and flagellated spermatozoids are located. The morphohistology of the analyzed testicles show similarities with those observed in other neotropical amphibians, being all the cells of the spermatogenic lineage in the same loculeMORFOHISTOLOGÍA TESTICULAR DE Hypsiboas pulchellus (AMPHIBIA, HYLIDAE).En este estudio se aportan datos sobre la morfohistología testicular de Hypsiboas pulchellus para conocer aspectos de su biología reproductiva. Las gónadas se procesaron empleando técnicas histológicas básicas, cortándose a 8 µm y tiñéndose con hematoxilina-eosina y tricrómico de Masson. Los testículos, ovoides y amarillentos de 4,64 ± 0,48 mm de largo por 2,05 ± 0,23 mm de ancho, están rodeados por la túnica albugínea que mide 5,60 ± 0,82 µm. Internamente presentan lóculos seminíferos de 257,47 ± 58,25 µm de diámetro, distinguiéndose en ellos cistos con células espermatogénicas asociadas a células de Sertoli. Existe escaso tejido intersticial. Las espermatogonias I son las células más grandes de la serie germinal (14,34 ± 1,74 µm), estas originan a las espermatogonias II (10,14 ± 1,33 µm). Los espermatocitos I presentan la cromatina levemente condensada midiendo 9,34 ± 0,32 µm. Los espermatocitos II miden 8,12 ± 1,07 µm. Las espermátidas I son esféricas, miden 7,61 ± 1,45 µm, agrupándose en cistos redondeados. Las espermátidas II, en cambio, son alargadas, no hallándoselas dentro de cistos (4,09 ± 0,51 µm). Los espermatozoides, alargados y flagelados, se hallan libres en el centro del lóculo. La morfohistología de los testículos analizados muestra características similares a las observadas en otros anfibios neotropicales, presentando todas las células del linaje espermatogénico en un mismo lóculo. Se propone profundizar y extender los análisis para determinar el tipo de ciclo gametogénico de estas poblaciones, los que serían, en principio, potencialmente continuos o discontinuos.